Different dimensions of oral health literacy are associated with social determinants of health in Brazilian adults - Luciana Reichert da Silva ASSUNÇÃO; Fabio Anevan Ubiski FAGUNDES; Helen Helene KUKLIK; Fernanda de Morais FERREIRA; Fabian Calixto FRAIZ (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract Social determinants of health (SDH) are strongly associated with oral health outcomes, and oral health literacy (OHL) is a potential factor that can modify this association. This study evaluated the association between SDH and OHL, including functional and interactive dimensions of OHL. The cross sectional study was conducted with 354 adults recruited from public dental clinics in southern Brazil. Functional OHL was measured using the Brazilian version of the Rapid Estimate of Adult Literacy in Dentistry (BREALD-30) and the Health Literacy Dental Scale (HeLD-14), for the evaluation of interactional OHL. SDH was evaluated through a structured questionnaire, and economic class was determined based on the Brazilian Economic Classification Criteria. The statistical analysis involved bivariate and multivariate Poisson regression with robust variance (α=0.05) to estimate rate ratios (RR) and 95% confidence intervals (CI). Among the 354 participants, 284 (80.2%) were women and the mean age was 22.9 ± 4.9 years. The median BREALD-30 score was 24 (1st/3rd quintile: 20/27) and the median HeLD-14 score was 45 (1st/3rd quintile: 37/50). Most participants had up to eight years of schooling (71.5%) and belonged to the "C" Economic Class or lower (94.1%). The multiple regression analysis showed that schooling and economic class were associated with the BREALD-30 and HeLD-14 scores, income and age were associated with the HeLD-14 score, and marital status and occupation were associated with the BREALD-30 score. Different dimensions of OHL were associated with SDH in Brazilian adults. This aspect should be incorporated into strategies for improving OHL levels in individuals or populations.